2015
DOI: 10.1089/lgbt.2014.0110
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Mediational Model of Outness, Social Support, Mental Health, and Wellness Behavior in Ethnically Diverse Lesbian, Bisexual, and Queer Women

Abstract: Purpose: A growing body of research has begun to examine wellness behaviors in sexual minority women. While a number of constructs have been associated with wellness behaviors in this population, including outness, social support, and mental health, no research has attempted to forge the specific and unique connections among them. The aim of the current study was to construct a theoretical chain among these variables leading to wellness behaviors among an ethnically diverse sample of sexual minority women. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 64 publications
(73 reference statements)
2
18
1
3
Order By: Relevance
“…Developing a gender that functions to resist stigma across psychological, cultural, interpersonal, and sexual domains does not mean that the external context of stigma disappears. In our research and that of others (e.g., Tabaac, Perrin, & Trujillo, 2015;Velez & Moradi, 2016), however, being out and active in LGBTQþ gender communities has been found to engender resilience and decrease distress. Tracking the social conditions that led to the generation and evolution of genders can help us to combat pathologizing narratives of people with diverse genders and to develop more accurate historical understandings of gender.…”
Section: How Do Genders Evolve Into Gender Identities and Communities?supporting
confidence: 50%
“…Developing a gender that functions to resist stigma across psychological, cultural, interpersonal, and sexual domains does not mean that the external context of stigma disappears. In our research and that of others (e.g., Tabaac, Perrin, & Trujillo, 2015;Velez & Moradi, 2016), however, being out and active in LGBTQþ gender communities has been found to engender resilience and decrease distress. Tracking the social conditions that led to the generation and evolution of genders can help us to combat pathologizing narratives of people with diverse genders and to develop more accurate historical understandings of gender.…”
Section: How Do Genders Evolve Into Gender Identities and Communities?supporting
confidence: 50%
“…In every study measuring sexual orientation disclosure, disclosure was associated with higher screening rates . It is unlikely that screening is a direct result of sexual identity disclosure, but more likely that providers who invite disclosure are also more likely to provide evidence‐based care to SMW or that SMW who disclose to providers also have stronger social support systems or more resources to mitigate the deleterious effects of potential discrimination in health care . Finally, findings from only one study in this review directly suggested that some health care providers misunderstand SMW's need for cervical cancer screening.…”
Section: Discussionmentioning
confidence: 88%
“…This heightened visibility can lead to mixed effects. Being out as a sexual or gender minority can provide social support leading to decreased distress (Tabaac, Perrin, & Trujillo, 2015;Velez & Moradi, 2016), but it also increases the likelihood of becoming a target of prejudice or violence (e.g., Puckett, Maroney, Levitt, & Horne, 2016). For instance, butch lesbians have been found to face discrimination, threats of violence, and experiences of violence more often than femme-identified or feminine lesbians (Levitt & Horne, 2002;Levitt, Puckett, Ippolito, & Horne, 2012).…”
Section: The Inter-related Oppressions Of Lgbtqþ Sexual and Gender MImentioning
confidence: 99%